The scope and sustainability of, and data about, utilization of embedded research: qualitative evidence from Latin America and the Caribbean - Victor Becerril-Montekio; Pilar Torres-Pereda; Luis Alberto García-Bello; Jacqueline Alcalde-Rabanal (Pan American Health Organization, 2024)
Objectives. This paper describes and analyzes embedded implementation research and the empirical processes of planning for utilization, strategies to promote utilization and the sustainability of utilization of results from research led by decision-makers in Latin America and the Caribbean. Methods. This qualitative, descriptive and interpretive study is based on the findings from semistructured interviews with members of teams working under the Embedding Research for the Sustainable Development Goals initiative (2018-2019) as well as their responses to a self-assessment follow-up questionnaire 1 year after the project was completed. Results. Altogether 13 teams from 11 countries participated in the Initiative. Nine teams had a core team composed of a decision-maker as the principal investigator assisted by a researcher as co-principal investigator. Four teams included more than one co-principal investigator; and in five teams, the originally assigned principal investigator was replaced. There was an interesting relationship between the expected utilization of research results, the utilization strategies, the sustainability of research uptake and the teams' collaboration modalities. When decision-makers and co-principal investigators were active participants, the intention to use the results and strategies for utilization were clearly oriented to improve implementation. In teams with basically a formal collaboration between the two principals, plans for utilization were unclear or focused on producing academic knowledge. The participation of implementers below the rank of principal investigator decision-maker may be relevant. Conclusions. Embedded implementation research is an innovative tool that may foster the utilization of research and strengthen health programs and services. Considering the internal dynamics of such research teams will enhance planning and strategies for research utilization as well as the sustainability of practical and actionable findings.